2008
DOI: 10.1016/j.cellsig.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential mediation of the Wnt canonical pathway by mammalian Dishevelleds-1, -2, and -3

Abstract: In the Drosophila, a single copy of the phosphoprotein Dishevelled (Dsh) is found. In the genomes of higher organism (including mammals), three genes encoding isoforms of Dishevelled (Dvl1, Dvl2, and Dvl3) are present. In the fly, Dsh functions in the Wnt-sensitive stabilization of intracellular beta-catenin and activation of the Lef/Tcf-sensitive transcriptional response known as the Wnt "canonical" pathway. In the current work we explore the expression of Dishevelleds in mammalian cells and provide an estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
125
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 53 publications
6
125
0
Order By: Relevance
“…Three genes encoding isoforms of Dishevelled (DVL1, DVL2, and DVL3) appear to function cooperatively as well as uniquely with respect to mediation of WNT3A-stimulated canonical signaling [42]. Therefore, it is possible to speculate that increased transcription of DVL2 in knee OA may result in increased Wnt-like signals.…”
Section: Discussionmentioning
confidence: 99%
“…Three genes encoding isoforms of Dishevelled (DVL1, DVL2, and DVL3) appear to function cooperatively as well as uniquely with respect to mediation of WNT3A-stimulated canonical signaling [42]. Therefore, it is possible to speculate that increased transcription of DVL2 in knee OA may result in increased Wnt-like signals.…”
Section: Discussionmentioning
confidence: 99%
“…This data, together with the fact that we show Dvl2 and 3 physically interact, suggests that Dvl2 and 3 form complexes and that both components are required in those complexes. Similarly, Lee et al (2008) showed that different Dvls can form complexes when co-expressed in the same cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dvl-2 is expressed abundantly in mammalian cells (27), binds to Equivalent amounts of cell lysates were incubated with GST-PBD or GST-RBD, and the amount of activated Rac1 or RhoA was determined by immunoblotting. Total cell lysates were immunoblotted with an anti-Rac1 or anti-RhoA antibody as a control.…”
Section: Apc Stimulates Dvl-2 Coassociation With β-Arrestins and Polymentioning
confidence: 99%